Review and prospect of research on ancient book information processing in China - Liu, Zhongbao; Qin, Zhenzhen; Zhao, Wenjuan (Malaysian Journal of Library and Information Science, 2021)
The advent of the era of big data appears to be an unprecedented opportunity to the development of ancient book information processing in China. A comprehensive review of the research on ancient book information processing can help researchers understand the research progress and grasp the future research trend. Based on the life cycle of ancient book information processing, this paper reviews and summarizes the progress of digital resource construction, data mining, system construction and information service, and prospects the future research trend. Although progress has been made to some extent, the ancient book information processing is still in its infancy. It is expected that more researchers will pay attention to and engage in this field.